POSSIBILITIES FOR ADAPTING SECURITY CULTURE MODEL AND ASSESSMENT TOOL FOR THE CORPORATE SECTOR: POSSIBILITIES FOR ADAPTING SECURITY CULTURE MODEL AND ASSESSMENT TOOL FOR THE CORPORATE SECTOR - Yankov, Vladimir (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2023)
Each organization forms a unique organizational culture in accordance with the intentions and behavior of management, social and business environment in which it operates, the characteristics of employees, the presence of subcultures, etc. The characteristics of the organizational culture that are relevant to security form the security culture in that organization. It is important to implement security culture model and assessment tools for proper management of the human factors involved in security. This article explores the possibilities to adapt the existing models of security culture and the tools for its assessment for the needs of corporate sector.